Media Effectiveness on Rural Women in Haryana for Vegetables Cultivation - Rani, Santosh; Lal, Makhan (Indian Journal of Extension Education, 2019)
The present study was conducted in four villages namely, Bhimnagar, Pali of Hisar and Milkpur and Bawanikhera of Bhiwani district of Haryana state. Fifty rural women involved in vegetable cultivation practices from each village were selected purposively, thus comprising a sample of 200 women. The impact of CD was found to be significant for gain in knowledge and change in attitude in all selected villages for all the messages regarding vegetable cultivation. There was a significant difference in the knowledge of rural women at pre and post exposure stage for all the messages. Education (r=0.257), income (r=0.241), landholding (r=0.179) and area under vegetables cultivation (r=0.180) had positive and significant relationship with knowledge acquisition. Attitude change of rural women was found to be positively and significantly related to education (r=0.296), landholding (r=0.180) and area under vegetable cultivation (r=0.185). Therefore, it may be inferred that respondents who were having cultivation as their main occupation, educated, having higher income, large landholders and more area under vegetable cultivation had acquired knowledge and favourable attitude when exposed them to CD on vegetable cultivation practices.
Keywords: C.D.; Attitude; Economics; Knowledge; Rural women; Vegetable